Caracterização morfológica e métodos para superação de dormência de sementes de Randia armata - Paulus, Rosani Inês (2005)
The study was carried through in a fishery of changes, in the city of Missal, State of Parana, in order to study the morphological characteristics of the plant, flower, fruit, seed and seedlings of lemon grass, Randia armata (De Candolle SW.) and treatments to overcome seed dormancy. To break dormancy study we used an experimental design of randomized blocks with four treatments, using 150 seeds in each treatment, six replicates of 25 seeds, totaling 600 seeds. Treatments consisted of untreated seeds (seeds washed in running water), mechanical scarification (sandpaper No. 100), heat (immersion in hot water at 80 ° C) and acid scarification (immersion in concentrated sulfuric acid 98% for ten minutes) . The seeds were subsequently submitted to germination in tubes. Through daily evaluations, we determined the percentage of germinated seeds and emergence speed index at 120 days. Randia armata is a woody shrub or small tree with thorns on the trunk. The fruit is fleshy, globe-shaped and the seed is surrounded by viscous mucilage. Germination is epigeous. Scarification with sulfuric acid proved the most effective treatment to promote germination of seeds of lemon grass.